VERBA PULL DALAM NOVEL PS I LOVE YOU KARYA CECELIA AHERN DAN TERJEMAHANNYA: KAJIAN SINTAKSIS DAN SEMANTIS - Dwinesa Anggraeni (Universitas Nasional, 2016)
ABSTRCT This research is entitled Verba Pull dalam novel PS I love You Karya Cecilia Ahern dan Terjemahannya:Kajian Sintaksis dan Semantis. This novel has been translated by Monica Dwi Chresnayani into Indonesianwith the same title. Syntactically, the aims of the research are to find out what elements that follow that followthe verb „Pull‟ and whether there is syntactic shift in the target language. While semantically, it is to find outthe verb „pull‟ translation and whether there is semantics shift from the source language into the targetlanguage. The method which is used in this research is descriptive-comparative method. The writer describes,compares, and analyzes the source language and the target language data, and then draws a conclusion fromthe analyses. Syntactically, the result of this research shows that the verb „pull‟ can be followed by somedifferent elements such as pull + object, pull + Preposition, pull+adverbial particle. Then, semantically, it isfound some meaning shift in the translation like the expansion meaning and enhancing meaning. In thetranslation, the writer also find some words that are not translated word by word but make a wordcombination, the verb „pull‟ + adverbial particles its called phrasal verbs.Key words: verb, novel, translation, syntactic, semantic